Little Tuna (Euthynnus affinis) Waste-Based Medium for Fungal Growth and The Lipolytic Activity - Prapti Sedijani; Dewa Ayu Citra Rasmi; Kusmiyati Kusmiyati; Ispa Irawati; Syamsul Bahri (Postgraduate, University of Mataram, 2022)
Lipase demand keeps increasing as it has wide applications in many sectors of industry, hence producing lipase is economically prospective. Finding a cheap medium is important for lipase production for commercial purpose. Waste based medium KIT1, KIT2 and KIT3 were alternately assessed for the capability to support growth and lipolytic activity of the fungi.Â SDA either or PDA were used as the control Medium. Fungi isolated from Coconut or Avocado flesh were used. Observation was made on day 1 and day 2 after inoculation. The result suggests that KIT2 gave similar growth and lipolytic activity to SDA medium, and better growth and lipolytic activity on KIT3 medium as compare to SDA and PDA